Facet Effect of Single-Crystalline Ag3PO4 Sub-microcrystals on Photocatalytic Properties - Bi, Yingpu; Ouyang, Shuxin; Umezawa, Naoto; Cao, Junyu; Ye, Jinhua (Journal of the American Chemical Society, 2011)
We recently reported that Ag3PO4 exhibits excellent photooxidative capabilities for O2 evolution from water and organic dye decomposition under visible-light irradiation. However, very little is known about the shape and facet effects of Ag3PO4 crystals on their photocatalytic properties. Herein we have developed a facile and general route for high-yield fabrication of single-crystalline Ag3PO4 rhombic dodecahedrons with only {110} facets exposed and cubes bounded entirely by {100} facets. Moreover, studies of their photocatalytic performance have indicated that rhombic dodecahedrons exhibit much higher activities than cubes for the degradation of organic contaminants, which may be primarily ascribed to the higher surface energy of {110} facets (1.31 J/m2) than of {100} facets (1.12 J/m2).